Local Regeneration of Dentin-Pulp Complex Using Controlled Release of FGF-2 and Naturally Derived Sponge-Like Scaffolds - Chiaki Kitamura; Tatsuji Nishihara; Masamichi Terashita; Yasuhiko Tabata; Ayako Washio (International Journal of Dentistry)
Restorative and endodontic procedures have been recently developed in an attempt to preserve the vitality of dental pulp after exposure to external stimuli, such as caries infection or traumatic injury. When damage to dental pulp is reversible, pulp wound healing can proceed, whereas irreversible damage induces pathological changes in dental pulp, eventually requiring its removal. Nonvital teeth lose their defensive abilities and become severely damaged, resulting in extraction. Development of regeneration therapy for the dentin-pulp complex is important to overcome limitations with presently available therapies. Three strategies to regenerate the dentin-pulp complex have been proposed; regeneration of the entire tooth, local regeneration of the dentin-pulp complex from amputated dental pulp, and regeneration of dental pulp from apical dental pulp or periapical tissues. In this paper, we focus on the local regeneration of the dentin-pulp complex by application of exogenous growth factors and scaffolds to amputated dental pulp.